Hepatic Hemangiomas Alter Morphometry and Impair Hemodynamics of the Abdominal Aorta and Primary Branches From Computer Simulations - Yin, Xiaoping; Huang, Xu; Li, Qiao; Li, Li; Niu, Pei; Cao, Minglu; Guo, Fei; Li, Xuechao; Tan, Wenchang; Huo, Yunlong (Frontiers in Physiology, 2018)
Background: The formation of hepatic hemangiomas (HH) is associated with VEGF and IL-7 that alter conduit arteries and small arterioles. To our knowledge, there are no studies to investigate the effects of HH on the hemodynamics in conduit arteries. The aim of the study is to perform morphometric and hemodynamic analysis in abdominal conduit arteries and bifurcations of HH patients and controls. Methods: Based on morphometry reconstructed from CT images, geometrical models were meshed with prismatic elements for the near wall region and tetrahedral and hexahedral elements for the core region. Simulations were performed for computation of the non-Newtonian blood flow using the Carreau-Yasuda model, based on which multiple hemodynamic parameters were determined. Results: There was an increase of the lumen size, diameter ratio and curvature in the abdominal arterial tree of HH patients as compared with controls. This significantly increased the surface area ratio of low time-averaged wall shear stress (i.e., SAR-TAWSS=〖"Surface area" 〗_("TAWSS≤4 dynes∙" 〖"cm" 〗^"-2" )/"Total surface area" ×100%) (24.1±7.9% vs. 5±6%, 11.6±12.8% vs. < 0.1%, and 44.5±9.2% vs. 21±24% at hepatic bifurcations, common hepatic arteries, and abdominal aortas, respectively, between HH and control patients). Conclusions: Morphometric changes caused by HH significantly deteriorated the hemodynamic environment in abdominal conduit arteries and bifurcations, which could be an important risk factor for the incidence and progression of vascular diseases.